Prevalence of surgical diseases of cattle in stall-fed and free-range cattle in Bangladesh (Bangladesh Veterinarian, 2014)
The prevalence of surgical diseases of 2081 cattle was studied from different free-ranging (Bathan) and stall-feeding systems. The overall prevalence of surgical disease of cattle was higher (53.2%) in Bathan than in the stall-feeding (37.5%) system. In Bathan, the most prevalent surgical diseases were myiasis (13.4%) followed by navel ill (12.5%), trauma (10.8%), claw diseases (7.6%), arthritis (6.1%), horn diseases (3.4%) and teat obstruction (2.6%). In stall-feeding system, the highest prevalence (10.6%) was claw diseases and navel ill (6.6%). Navel ill, hernia, arthritis, horn diseases, urolithiasis and tail gangrene were more prevalent in male; and claw diseases, trauma, myiasis, upward patellar fixation and dislocation of hip joint were more prevalent in female cattle. Most diseases were more prevalent in summer but claw diseases, urolithiasis and teat crack were more prevalent in winter. Clean environment is needed to reduce the prevalence of such problems. DOI: http://dx.doi.org/10.3329/bvet.v30i2.18256 Bangl. vet. 2013. Vol. 30, No. 2, 62-69